International validation of the low anterior resection syndrome score - Juul, Therese; Ahlberg, Madelene; Biondo, Sebastiano; Emmertsen, Katrine Jossing; Espin, Eloy; Jimenez, Luis Miguel; Matzel, Klaus; Palmer, Gabriella; Sauermann, Anna Catherin; Trenti, Loris; Zhang, Wei; Laurberg, Soren; et al. (Annals of Surgery, 2014)
The aims of this study were to investigate the convergent and discriminative validity and reliability of the low anterior resection syndrome (LARS) score in an international setting.The LARS score is a simple self-administered questionnaire measuring bowel dysfunction after rectal cancer surgery. The score is intended to be commonly used in international research and clinical practice in the future. Therefore, a thorough validation in an international setting is of utmost importance.The LARS score was translated using methods in keeping with current international recommendations. A total of 801 patients operated for rectal cancer in Sweden, Spain, Germany, and Denmark completed the LARS score questionnaire, including an anchor question assessing the impact of bowel function on quality of life. A subgroup of 218 patients completed the LARS score twice. Data were analyzed per country.The LARS score has demonstrated a high convergent validity in terms of a high correlation between LARS score and quality of life (P < 0.001). Sensitivity ranged from 67.7% to 88.3% and specificity from 58.1% to 86.3%. The LARS score was able to discriminate between groups of patients differing with regard to radiotherapy, surgery, and age (P < 0.05). The score also demonstrated high reliability at test-retest with narrow limits of agreement and no statistically significant difference between scores at the first and second test.The Swedish, Spanish, German, and Danish versions of the LARS score have proven to be valid and reliable tools for measuring LARS in European rectal cancer patients.
EVALuna2:15141